LEGITIMASI PEMBERHENTIAN KEANGGOTAAN DPR/DPRD OLEH PARTAI POLITIK HASIL PEMILU LEGISLATIF DENGAN SISTEM PROPORSIONAL TERBUKA - Taufikkurrahman Taufikkurrahman (Research Institute and Community Engagement of IAIN MADURA, 2018)
This writing is analyzing the legitimacy of political party in retiring its member who still becomes the member of the representative of legislative council (DPR/ DPRD) and these representatives are chosen by the legislative general election openly and proportionally conducted by the nation. Openly proportional system is understood as the model of people’s sovereignty. It happens when the candidates are most voted as the member of representative of legislative council. Openly proportional system is done by displaying the political parties as the members of general election and then they propose some candidates of legislative members to be chosen directly by Indonesian people. The most voted representatives will be chosen as the member of legislative council (DPR/ DPRD). When there is a party retires their own representative, do they have their own legalization and is it contradictory with the concept of Indonesian people’s sovereignty? This writing is using juridical normative method by analyzing some constitutions; they are general election constitution, political party constitution, and constitution of MD3. According to the constitution, retirement by the political party has already have its own legitimacy because the constitution gives the authority, but the retirement is contradictory with the spirit of people’s sovereignty because the people have the absolute right of their own vote.